A Comprehensive Literature Review of Relationship of Insuline Resistance and Thyroid Cancer - Erick Persson Jeffry; Charles Sanjaya Seikka (The International Journal of Medical Science and Health Research, 2025)
Background: The relationship between insulin resistance and thyroid cancer has garnered increasing attention in recent years, as emerging evidence suggests a complex interplay between metabolic disorders and cancer risk. Literature Review: The study by (Malaguarnera et al., 2012) outlines the role of insulin and IGFs in promoting cell proliferation and migration, implicating these factors in tumorigenesis. This perspective is echoed in the literature review by (Shih et al., 2012), which discusses the rising incidence of thyroid cancer, particularly in small tumors, and emphasizes the need to investigate the role of diabetes and metabolic syndrome further. The meta-analysis conducted by (Yeo et al., 2014) reinforces the association between diabetes and thyroid cancer, suggesting that insulin resistance may be a significant contributor to this risk. Meanwhile, (Chiefari et al., 2021) explores the mechanisms linking chronic hyperinsulinemia to cancer development, emphasizing the importance of inflammatory processes in this relationship. Recent research by (Xu et al., 2022) specifically isolates the effects of insulin resistance in euthyroid patients, further supporting the notion that insulin resistance is a risk factor for differentiated thyroid cancer. Lastly, (Wu et al., 2024) synthesizes the current understanding of diabetes and thyroid cancer, identifying several mechanisms, including oxidative stress and hyperinsulinemia, that may underlie this association. Conclusion: In conclusion, the reviewed literature collectively underscores the significance of insulin resistance as a potential risk factor for thyroid cancer. It highlights the need for further studies to elucidate the biological mechanisms involved and to explore the implications for prevention and treatment strategies. The complexity of the relationship between metabolic disorders and cancer risk suggests that a multi-faceted approach is necessary for future research.